Efficient Client-to-Client Password Authenticated Key Exchange - YANG, Yanjiang (Institutional Knowledge at Singapore Management University, 2008)
With the rapid proliferation of client-to-client applications, PAKE (password authenticated key exchange) protocols in the client-to-client setting become increasingly important. In this paper, we propose an efficient client-to client PAKE protocol, which has much better performance than existing generic constructions. We also show that the proposed protocol is secure under a formal security model.